IS INDONESIA MORE FINANCIALLY LINKED TO THE WORLD SINCE THE ASIAN FINANCIAL CRISES? - lestari, esta (P2E-LIPI, 2012)
The 1997-98 Asian financial crises brought significant changes to theIndonesian economy. The contagion originated in Thailand and spreadthroughout the region, indicating interdependencies of the Indonesianeconomy with the worldâs economies but especially with those in the region.The crisis was channelled through the financial sector, which is assumed tobe the most open sector in the economy. As a result, reform began andchanges took place in many sectors and in the policies that guided them. Howthe financial integration changed over 15 years of reform is the main interestof this study. Specifically, this study analyses the changing financialintegration in stock markets following the Asian crises. Therefore, the periodof the study is in five parts, based on the origins of the US subprime andEuropean crises. Using a quantitative approach, this study employsmultivariate EGARCH-M(1,1) models. These models allow us to examinedifferent effects of positive and negative news on financial risk in stock prices.Daily stock data are used from the Jakarta Stock Exchange (JKSE), theSingapore Exchange (STI), the Kuala Lumpur Stock Exchange (KLSE), theShanghai Composite Index (SSE), Nikkei 225 (NIKK) (Japan), the KoreaStock Exchange (KOSPI), the Bombay Stock Exchange (SENSEX), theGerman stock exchange (DAX), the London FTSE, and Standard and PoorâsUS (SP). The result of this study provides the figures showing thedevelopment of Indonesian financial-market linkage to other countries and willhelp the government to be aware of crises that are initiated by externalfactors, and to be able to manage future crises.